2016
DOI: 10.1093/nutrit/nuv103
|View full text |Cite|
|
Sign up to set email alerts
|

Role of maternal vitamins in programming health and chronic disease

Abstract: Vitamin consumption prior to and during pregnancy has increased as a result of proactive recommendations by health professionals, wide availability of vitamin supplements, and liberal food-fortification policies. Folic acid, alone or in combination with other B vitamins, is the most recommended vitamin consumed during pregnancy because deficiency of this vitamin leads to birth defects in the infant. Folic acid and other B vitamins are also integral components of biochemical processes that are essential to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 111 publications
0
16
0
1
Order By: Relevance
“…We have found studies that report a positive association for vitamin B2 [ 53 ], B9 [ 23 , 26 , 28 ], and B12 [ 23 , 28 , 39 ], while others have found an absence of effect for vitamin B9 [ 24 , 27 , 52 , 54 ] and B12 [ 24 , 26 , 54 ]. Our data, in contrast, show a protective effect for B9 and B12, both of which have an important role in supporting maternal and fetal health during pregnancy to build and preserve maternal stores and meet the needs of rapidly growing tissues [ 55 ] and increase the risk of neural tube defects and may contribute to preterm birth [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have found studies that report a positive association for vitamin B2 [ 53 ], B9 [ 23 , 26 , 28 ], and B12 [ 23 , 28 , 39 ], while others have found an absence of effect for vitamin B9 [ 24 , 27 , 52 , 54 ] and B12 [ 24 , 26 , 54 ]. Our data, in contrast, show a protective effect for B9 and B12, both of which have an important role in supporting maternal and fetal health during pregnancy to build and preserve maternal stores and meet the needs of rapidly growing tissues [ 55 ] and increase the risk of neural tube defects and may contribute to preterm birth [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that obese mothers might be at higher risk of SGA as well, but such an association is not observed consistently [13, 14]. There have been numerous reviews of the effects of dietary, exercise and lifestyle interventions on birthweight [13, 1518], as well as associations between dietary intake and birthweight [13, 1921]. However, these have not addressed why fetal growth is normal in many obese and diabetic pregnancies but altered in others [22].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple methyl donor nutrients and cofactors (highlighted in gray, Figure 1) are essential nutrients provided solely by the diet. Studies have shown that deficiency, imbalance or excess of one of more of these nutrients throughout various periods of life can alter development, cognition and disease risk (Pannia et al 2016; Veena et al 2016; Morris 2012; Reynolds 2006; O’Neill et al 2014). We previously reported that MDS given concurrently with a 60% HF diet during pregnancy and lactation normalizes palatable food preference, increases locomotor activity, and normalizes gene expression and both gene specific and global DNA hypomethylation in male and female offspring (Carlin et al 2013).…”
Section: Introductionmentioning
confidence: 99%